EXPLORING THE IMPACT OF SOCIOECONOMIC BACKGROUND ON ACCESS TO HIGHER EDUCATION: A QUALITATIVE STUDY IN PAKISTAN - Dr. Shakeel Ahmed; Dr. Fazli Wadood; Mamoona Anam; Dr. Ausima Sultan; Bashir Khan; Zubair Hussain (International Journal of Contemporary Issues in Social Sciences, 2024)
This qualitative study investigates the complex relationship between socioeconomic background and access to higher education in Pakistan. To get a range of perspectives on this crucial subject, 500 people—including parents, educators, legislators, and students—were involved in the study. The study's introduction highlights the importance of understanding the challenges faced by students from varied socioeconomic backgrounds in their pursuit of higher education, given its impact on social mobility and economic growth. Focus groups and in-depth interviews were among the many qualitative data sources gathered for the study using a multi-method approach. By employing a deliberate sample of participants to ensure coverage across genders, socioeconomic categories, and geographic places, the study's depth and breadth were expanded. Data analysis led to several significant findings. Seventy-five percent of participants cited expensive tuition as a key obstacle, suggesting that financial constraints posed a significant hurdle. Cultural and societal attitudes had a major role in shaping participants' educational decisions, with women being the majority affected by these attitudes at 65%. Further barriers to higher education were identified as information shortages, institutional policies, and disparities in secondary school quality. The study's conclusion highlights how urgently these barriers need to be addressed through policy changes. Recommendations include developing options for accessible postsecondary education, expanding financial aid programs, and promoting gender equity and cultural inclusivity in order to ensure that all Pakistanis have fair access to higher education.